2019
DOI: 10.3390/agronomy9060327
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Biochar to a Sandy Desert Soil: Effect on Crop Growth, Water Retention and Selected Properties

Abstract: Agricultural and environmental applications of biochar (BC) to soils have received increasing attention as a possible means of improving productivity and sustainability. Most previous studies have focused on tropical soils and more recently temperate soils. However, benefits of BC addition to desert soils where many productivity constraints exist, especially water limitations, have not been widely explored. Thus, three experiments were designed using a desert soil from Saudi Arabia to address three objectives:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 70 publications
(174 reference statements)
5
51
0
Order By: Relevance
“…Growing In agreement with earlier results reported by Khaled and Schoenau [55] and Laghari et al [44], the application of biochar produced at low temperature (B400) leads to higher biological yield compared to the control treatment and biochar produced at higher temperatures (B600) in a sandy-loam growing substrate. Olmo et al [56], who worked with olive-tree pruning-derived biochar, found significant differences for biochar application in root morphology as a result of the effect on some nutrient availability and the subsequent fine root proliferation.…”
Section: Grain Productionsupporting
confidence: 90%
“…Growing In agreement with earlier results reported by Khaled and Schoenau [55] and Laghari et al [44], the application of biochar produced at low temperature (B400) leads to higher biological yield compared to the control treatment and biochar produced at higher temperatures (B600) in a sandy-loam growing substrate. Olmo et al [56], who worked with olive-tree pruning-derived biochar, found significant differences for biochar application in root morphology as a result of the effect on some nutrient availability and the subsequent fine root proliferation.…”
Section: Grain Productionsupporting
confidence: 90%
“…Soil Moiture Content could be higher due to differences in BD between treatments, because higher BD decreased the spaces where water could be retained. The same results were documented by Alotaibi andSchoenau (2019), Jindo, Mizumoto, Sawada, Sánchez-Monedero, andSonoki (2014), and Omondi et al (2016). Akhtar, Andersen, and Liu (2015) reported that B fertilization might be used as a mitigating factor for improving water storage in soil.…”
Section: Discussionsupporting
confidence: 76%
“…Akhtar, Andersen, and Liu (2015) reported that B fertilization might be used as a mitigating factor for improving water storage in soil. However, the effect of biochar is directly proportional to biochar rate, soil texture, and pyrolysis temperature (Alotaibi & Schoenau, 2019). The addition of biochar and nitrogen significantly improved the soil chemical properties, that is, pH, SOC, TN, AP, and AK (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current study indicate that fresh PSB together with RNPK significantly increases soil water retention (Table 9), relative to the RP alone or PSB alone or CT (non-inoculant control). These results are supported by a number of other studies [68,69]. The difference observed in higher water retention in PSB together with RNPK might be due to slow water movement by PSB colonialization in the column ( Figure 3A) against different time durations compared to other treatments.…”
Section: Slsupporting
confidence: 89%
“…In the end, when we compared the impact of fresh PSB and incubated PSB on sandy soil, it was clear that fresh PSB may be hydrophobic and then hydrophilic when PSB is incubated with prolonged contact with moist sandy soil, as was observed in other past studies [63,68,70,71]. The correlation amonf differet studied parameter are given in the Table 9.…”
Section: Slsupporting
confidence: 54%